Chemical Literacy and Students’ Conceptual Understanding and Effective Learning Strategies in a Global Perspective: A Systematic Literature Review - Islawati Islawati; Eli Rohaeti; Erfan Priyambodo (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze chemical literacy and students’ conceptual understanding, as well as to identify effective learning strategies from a global perspective. The method employed is a Systematic Literature Review (SLR) using the PRISMA approach on scientific articles indexed in Scopus within the period of 2015–2025. Based on the selection process, a total of 11 articles met the inclusion criteria and were analyzed using narrative synthesis and thematic analysis based on three main focuses: the development of chemical literacy, its relationship with conceptual understanding, and instructional approaches. The findings indicate that chemical literacy is a multidimensional construct encompassing knowledge, skills, attitudes, and the ability to apply concepts in real-life contexts, and it has evolved toward critical chemical literacy grounded in global issues. Furthermore, the results reveal that the level of students’ chemical literacy remains relatively low across various countries and is closely related to their conceptual understanding of chemistry. Various instructional approaches, such as context-based learning, socio-scientific issues (SSI), STEAM, argumentation, and technology integration, have been proven effective in enhancing both chemical literacy and conceptual understanding. In conclusion, chemical literacy and conceptual understanding are interrelated constructs that should be developed integratively through contextual and innovative learning approaches to address global challenges.